Analisis Is Structure and Vegetation Composition Increases Tree and Pillar at Hutan Lindung Oereu Village Bani Bani Is Io Kufeudistrict Malacca Regency - Niis, Angela (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2020)
The purpose of this study was to determine the tree and pole-level plant species found in the Oereu Protected Forest Bani-Bani Village Io Kufeu District of Malacca District, To find out the structure and composition of tree-level plant vegetation and poles found in the Oereu Protected Forest in the Bani-Bani Village District of Io Kufeu District of Malacca, and To implement research on the structure and composition of tree and pole level vegetation in the Oereu Protection Forest of Desa Bani-Bani District of Io Kufeu District of Malacca in learning biology in schools. The method used in this study is the quadratic method by placing a plot beside the transect line. At each transect line, 5 observation plots were placed with the size of each plot 20 mx 20 m = 400 m2 for tree level, and 10 mx 10 m = 100 m2 for pole level, with a distance between plots 25 m. analyzing the structure and composition of tree-level vegetation, and poles found at research sites, namely by calculating absolute density, relative density, absolute frequency, relative frequency, basal area, relative basal area, and important value index. The results of the study were found as many as 13 types of plants consisting of 11 families. When looking at the importance value index at tree level vegetation, the highest important value index is Tectona grandis, L, 57.35%, while the one with the lowest important value index is Alstonia scholaris, L 13.22%, and at pole level vegetation, the index value the highest importance is Tectona grandis, L, 36.33%, while the one with the lowest important value index is Leucena lenccophalla, 16.25%. The type of vegetation that has the highest important value index is because it has a fairly high distribution ability and can adapt well to its environment.